Formação de Professores: uma análise da relevância da disciplina língua brasileira de sinais como parte do currículo do Curso de Educação do Campo de Tocantinópolis - TO - Sousa, Géssica Milena Simith (Universidade Federal do Tocantins, 2022)
The present work addresses issues in the area of teacher rural education course, with an emphasis on the relevance of Libras-Brazilian sign language discipline as part of the curriculum of the field education course-with qualification in arts and music- LEDOC and its contributions in the lives of future teachers when they are in full exercise of teaching. We started from the following research question, a single Libras subject with a workload of 60 hours, divided into University time and community time, will be enough for future teachers to acquire basic pedagogical and linguistic knowledge that will provide them with skills and competences necessary for the good care of deaf students, when they are in full exercise of teaching? In order to answer this question, we made use of the following general objective of our work is to understand the relevance of the Libras discipline in the training of teachers in the degree course in Rural Education, which is anchored by three specific objectives, namely, i) describe the pedagogical practices developed by teachers of the Libras discipline of the field education course during university time; ii) to know the perception of the graduating and repeating students of the Libras discipline about the workload and the format of the discipline with the divisions in university time and community time; iii) present inputs that allow us to infer on the need to expand the workload or even the change in the format of the Libras subject in the curriculum of the field education course on the Tocantinópolis campus. The methodological process is characterized as a research with a qualitative seal and bibliographic and documentary characteristics, in addition to including a questionnaire. After discussing theoretically in three chapters, we arrived at the results of our work, where we found that most LEDOC students do not feel prepared to assist deaf students. It was also found that the Libras subject contributes positively to the academic formation of future teachers, providing them with knowledge that will be of paramount importance in the care of deaf students in regular education, however, with this study, it was noticed that it is necessary to rethink about a possible increase in the workload of the Libras subject.